Best Practice No 176: Updated recommendations for HER2 testing in the UK. Issue 3 (27th February 2004) - Ellis, I O; Bartlett, J; Dowsett, M; Humphreys, S; Jasani, B; Miller, K; Pinder, S E; Rhodes, A; Walker, R
Abstract : This paper serves to update previously published guidance on rationale and methodology for HER2 laboratory testing following the recommendation for the use of HER2 targeted treatment in the management of advanced breast cancer in the UK. Emphasis is placed on the standardisation of methodology and assessment and strategies to achieve high quality performance. A two phase testing algorithm based on first line immunocytochemistry evaluation and second line fluorescence in situ hybridisation assessment of borderline cases is recommended. To ensure maintenance of expertise, an annual caseload volume of at least 250 cases is recommended for laboratories providing a testing service.